Characterization of the liquid intermediates from gasification of lignite in supercritical water: Insights into the gasification process for hydrogen production. (19th October 2016) - Yu, Jiangdong; Chen, Qiuling; Guan, Qingqing; Li, Bin; Ning, Ping; Gu, Junjie; Lu, Xiuyun
Abstract: The liquid intermediates formed during supercritical water gasification of lignite have a significant influence on the process. To deeply understand the process, the effects of various process parameters on the components and their distribution in liquid intermediates were examined by GC–MS and FT–IR. GC–MS analysis indicated that the liquid intermediates can be principally grouped as alkenes, alkanes, aromatic hydrocarbons, phenols and oxygen containing compounds. Without adding Ru catalyst, the relative area % of aromatic hydrocarbons, phenols and oxygen containing compounds showed little changes, while that of alkanes increased and alkenes decreased with increasing time and temperature. In contrast, all the percentage area of intermediates, except aromatic hydrocarbons, decreased sharply with Ru catalyst. The unconverted aromatic hydrocarbons mainly consist of p-xylene (15.28%), o-xylene (12.87%), mesitylene (5.99%), naphthalene (8.96%), methylnaphthalene (3.88%), indicating these aromatic hydrocarbons can be regarded as the 'last hurdle' to get over for complete gasification of lignite in SCW. FT–IR experimental results correlated well with that obtained by GC–MS. According to the obtained results and previous studies, a simplified schematic diagram illustrating the possible reaction pathways for gasification of lignite in SCW with Ru catalyst was proposed to further understand the SCWG of lignite. Highlights: Liquid intermediates from SCWG of lignite were characterized. Effects of various process parameters on the liquid intermediates were examined. A schematic diagram for SCWG of lignite was proposed.